Anthocyanin supplementation in alleviating thrombogenesis in overweight and obese population: A randomized, double-blind, placebo-controlled study. (May 2017) - Thompson, Kiara; Pederick, Wayne; Singh, Indu; Santhakumar, Abishek Bommannan
Highlights: Anthocyanins reduce platelet aggregation in obese/overweight population. Anthocyanins alleviate platelet activation-dependant surface marker expression. Anthocyanins modulate mechanisms involved in thrombogenesis. Anthocyanins displays potential as a complementary antiplatelet therapeutic. Abstract: The aim was to evaluate the effect of anthocyanin (ACN) supplementation in reducing thrombogenesis and maintaining hemostasis in pro-thrombotic overweight and obese individuals. Twenty-six (M = 9, F = 17) overweight/obese (BMI > 25) individuals participated in this randomized, double-blind, placebo-controlled, crossover design dietary intervention trial. Volunteers consumed ACN (320 mg/day) or placebo capsules for 28-days followed by a two-week wash-out period. ACN supplementation inhibited adenosine diphosphate (ADP)-induced platelet activation-related conformational change and degranulation by reducing PAC-1 expression by 12% and P-selectin expression by 9% respectively. ACN supplementation also alleviated thrombogenic progression by reducing monocyte-platelet aggregate formation by 29% and platelet endothelial cell adhesion molecule-1 (PECAM-1) expression by 21%. Platelet aggregation induced by ADP, collagen and arachidonic acid was reduced by 36%, 17%, and 24% respectively. ACN supplementation has the potential to reduce the risk of thrombosis in overweight/obese population by targeting specific pathways of platelet activation/aggregation and endothelial dysfunction associated leucocyte migration.